Is time of birth a predictor of adverse perinatal outcome? A hospital-based cross-sectional study in a low-resource setting, Tanzania - Andrew Mgaya; Januarius Hinju; Hussein Kidanto (BMC, 2017)
Abstract Background Inconsistent evidence of a higher risk of adverse perinatal outcomes during off-hours compared to office hours necessitated a search for clear evidence of an association between time of birth and adverse perinatal outcomes. Methods A cross-sectional study conducted at a tertiary referral hospital compared perinatal outcomes across three working shifts over 24 h. A checklist and a questionnaire were used to record parturients' socio-demographic and obstetric characteristics, mode of delivery and perinatal outcomes, including 5th minute Apgar score, and early neonatal mortality. Risks of adverse outcomes included maternal age, parity, referral status and mode of delivery, and were assessed for their association with time of delivery and prevalence of fresh stillbirth as a proxy for poor perinatal outcome at a significance level of p = 0.05. Results Off-hour deliveries were nearly twice as likely to occur during the night shift (odds ratio (OR), 1.62; 95% confidence interval (CI), 1.50-1.72), but were unlikely during the evening shift (OR, 0.58; 95% CI, 0.45-0.71) (all p < 0.001). Neonatal distress (O.R, 1.48, 95% CI; 1.07-2.04, p = 0.02), early neonatal deaths (OR, 1.70; 95% CI, 1.07-2.72, p = 0.03) and fresh stillbirths (OR, 1.95; 95% CI, 1.31-2.90, p = 0.001) were more significantly associated with deliveries occurring during night shifts compared to evening and morning shifts. However, fresh stillbirths occurring during the night shift were independently associated with antenatal admission from clinics or wards, referral from another hospital, and abnormal breech delivery (OR 1.9; 95% CI, 1.3-2.9, p = 0.001, for fresh stillbirths; OR, 5.0; 95% CI 1.7-8.3, p < 0.001, for antenatal admission; OR, 95% CI, 1.1-2.9, p < 0.001, for referral form another hospital; and OR 1.6; 95% CI 1.02-2.6, p = 0.004, for abnormal breech deliveries). Conclusion Off-hours deliveries, particularly during the night shift, were significantly associated with higher proportions of adverse perinatal outcomes, including low Apgar score, early neonatal death and fresh stillbirth, compared to morning and evening shifts. Labour room admissions from antenatal wards, referrals from another hospital and abnormal breech delivery were independent risk factors for poor perinatal outcome, particularly fresh stillbirths.